Emerging Memory and Computing Devices in the Era of Intelligent Machines - Khalili, Pedram (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Computing systems are undergoing a transformation from logic-centric towards memory-centric architectures, where overall performance and energy efficiency at the system level are determined by the density, performance, functionality and efficiency of the memory, rather than the logic sub-system.